Mengeksplorasi Strategi Pendidikan Profesional Guru Kelas terhadap Penggunaan Media Interaktif Berupa Video Pembelajaran - FardyanSyah (Tarbawi, 2025)
Interesting learning is interactive learning or two-way communication between teachers and students in the learning process. Teacher strategies in learning play an important role in facing the current technological era, which not only emphasizes the delivery of material but can create an interesting and enjoyable learning atmosphere. This research aims to create a classroom teacher strategy towards the use of technology as learning. The findings of this study can show that learning strategies in this technological era must be interactive or two-way communication between teachers and students, in addition to suitable learning strategies direct application is the key to the success of the learning process in the current era By combining classroom teacher strategies with the use of technology in learning aims to make Islamic educational institutions / institutions can develop well. Therefore, an effective strategy is needed with the use of technology in learning.